Capital Market Predictive Power on the Development of the Nigerian Economy: An Impulse Response and Variance Decomposition Approach (Global Journal of Human-Social Science, 2019)
The study investigates the contributions of Nigeria s capital market to the development of Nigeria economy Most researchers focused on the capital market and growth nexus while we deviated by focusing on the role played by the capital market in ensuring the reduction of unemployment and poverty in Nigeria Specifically we investigated the contributions of market capitalization MCAP the value of share traded VST and all share index ASI to the unemployment rate UNPR and poverty NPI reductions in Nigeria within the period 1981 to 2017 The data series used was obtained from the annual statistical bulletin of the central bank of Nigeria CBN and Nigeria stock exchange NSE Preliminary analyses of stationarity and cointegration tests revealed that the series was non stationary at levels and cointegrated respectively
Keywords: capital market; sustainable development; impulse response function; variancede composition